The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jpn.12292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different dietary zinc levels on cashmere growth, plasma testosterone level and zinc status in male Liaoning Cashmere goats

Abstract: The experiment was conducted to investigate the influence of different levels of zinc (Zn) on cashmere growth, plasma testosterone and Zn profile in male Cashmere goats. Twenty-eight male Liaoning Cashmere goats, 3 years old and body weight at 56.2 ± 2.45 kg, were assigned to four groups. The animals were fed a basal diet containing of 45.9 mg Zn/kg dry matter (DM) basis and supplemented with 0, 20, 40 or 80 mg Zn (reagent grade ZnSO₄ ·7H₂ O) per kg DM for 90 days. There was no significant effect on growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The lower ALP activity of the control lambs is consistent with the study of Cho et al [49] who reported decreased ALP activity in Zn-deficient animals. The present results are also in agreement with Liu et al [50] who observed a significant increase in ALP activity due to dietary Zn in goats fed a basal diet (containing 45.9 mg Zn/kg) supplemented with 20, 40, or 80 mg Zn/kg. Similarly, Kumar et al [51] observed a significant increase in ALP activity attributed to dietary Zn in bulls fed a basal diet (containing 32.5 mg Zn/kg) supplemented with 35 or 70 mg Zn/kg.…”
Section: Blood Hormones and Enzymessupporting
confidence: 93%
“…The lower ALP activity of the control lambs is consistent with the study of Cho et al [49] who reported decreased ALP activity in Zn-deficient animals. The present results are also in agreement with Liu et al [50] who observed a significant increase in ALP activity due to dietary Zn in goats fed a basal diet (containing 45.9 mg Zn/kg) supplemented with 20, 40, or 80 mg Zn/kg. Similarly, Kumar et al [51] observed a significant increase in ALP activity attributed to dietary Zn in bulls fed a basal diet (containing 32.5 mg Zn/kg) supplemented with 35 or 70 mg Zn/kg.…”
Section: Blood Hormones and Enzymessupporting
confidence: 93%
“…When compared with critical levels for Cu (<10 ppm) and Zn (<100 ppm), 50 and 100% cows showed sub-normal levels in hair samples indicating their dietary deficiency. It has been demonstrated in several studies that concentration of Zn in hair is correlated with dietary Zn intake [35, 36]. Studies have shown the level of Zn in hair on normal diet to be 120–150 ppm in dairy cows [1].…”
Section: Resultsmentioning
confidence: 99%
“…One study with goats showed that serum testosterone concentration was increased by zinc intake in the goats' diet for 90 days, and the testosterone concentration was higher in the goats fed the diet supplemented with zinc compared with those fed a basal diet. 23 In humans, a study of hemodialyzed men with low serum zinc concentration and low sexual function showed dialytic administration of zinc increased serum testosterone concentration. 24 A double-blind study with hemodialyzed men also showed that intake of 50 mg of zinc per day for 6 months significantly increased serum concentrations of both testosterone and zinc in men in the zinc-treated group but not in those receiving a placebo.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been several studies regarding the effect of zinc intake on testosterone production. One study with goats showed that serum testosterone concentration was increased by zinc intake in the goats' diet for 90 days, and the testosterone concentration was higher in the goats fed the diet supplemented with zinc compared with those fed a basal diet 23 . In humans, a study of hemodialyzed men with low serum zinc concentration and low sexual function showed dialytic administration of zinc increased serum testosterone concentration 24 .…”
Section: Discussionmentioning
confidence: 99%